Pengangkatan Anak Berdasarkan Kesejahteraan Anak: Suatu Studi Tentang Perkembangan Hukum, Permasalahan Pada Faktor Perundang-Undangan Tentang Berfungsinya Hukum Pada Hukum Pengangkatan Anak - Setiono, - (1999)
This research aims at studying (1) to what extent the legislation of child adoption regulates the fulfilment of children;s welfare, (2) to what extent court decisions (in the field of child adoption) are made for the sake of children’s welfare, (3) How the legislation and or court decisions in child adoption affect the existing problems in the factor of legislation with respect to how the law functions.